Dose reduction and image quality improvement of chest radiography by using bone-suppression technique and low tube voltage: a phantom study. - Takagi, Satoshi; Yaegashi, Tatsuya; Ishikawa, Masayori (European Radiology, 2020)
Objective: To clarify the relationship between entrance surface dose (ESD) and physical image quality of original and bone-suppressed chest radiographs acquired using high and low tube voltages.Methods: An anthropomorphic chest phantom and a 12-mm diameter spherical simulated nodule with a CT value of approximately + 100 HU were used. The lung field in the chest radiograph was divided into seven areas, and the nodule was set in a total of 66 positions. A total of 264 chest radiographs were acquired using four ESD conditions: approximately 0.3 mGy at 140 and 70 kVp and approximately 0.2 and 0.1 mGy at 70 kVp. The radiographs were processed to produce bone-suppressed images. Differences in contrast and contrast-to-noise ratio (CNR) values of the nodule between each condition and between the original and bone-suppressed images were analyzed by a two-sided Wilcoxon signed-rank test.Results: In the areas not overlapping with the ribs, both contrast and CNR values were significantly increased with the bone-suppression technique (p < 0.01). In the bone-suppressed images, these values of the three conditions at 70 kVp were equal to or significantly higher than those of the condition at 140 kVp. There was no apparent decrease in these values between the ESD of approximately 0.3 and 0.1 mGy at 70 kVp.Conclusion: By using the shortest exposure time and the lowest tube voltage possible not to increase in blurring artifact and image noise, it is possible to improve the image quality of bone-suppressed images and reduce the patient dose.Key Points: • The effectiveness of bone-suppression techniques differs in areas of lung field. • Image quality of bone-suppressed chest radiographs is improved by lower tube voltage. • Applying lower tube voltage to bone-suppressed chest radiographs leads to dose reduction.